Antitrust by Other Means: Haley on Form and Function - Salil K. Mehra (Washington University Global Studies Law Review, 2009)
To understand how Haley’s work remains relevant, it is worth noting three important aspects of what his research did. First, he managed to articulate a conception of comparative antitrust law during a time when antitrust was often cast as a largely American show. Second, he demonstrated the importance of institutions and legal infrastructure to antitrust law, and how antitrust might function with remedies other than our own. Finally, he explicated the role of politics and political theory in providing a basis for antitrust within a society.
Keywords: Antitrust law; Comparative law; John Owen Haley; International; Japan; United States